Pengolahan Limbah Cair Industri Pakan Ternak dengan Kombinasi Proses Aerasi dan Biologi Aerob - Sumada, Ketut; Chaerani, Novika Cahya; Priambodo, Melandy Dwi; Saputro, Erwan Adi (Jurnal Teknologi Lingkungan, 2021)
ABSTRACT Wastewater is unclean and contains various substances that can risk the lives of humans and animals. This waste usually comes from the results of human actions (including industrialization). Industry must apply the principle of waste control in a careful and integrated system. Aeration is one of the most widely used techniques for improving the physical and chemical characteristics of wastewater. The aerobic microbiological wastewater treatment process utilizes aerobic microbial activity in aerobic conditions to decompose organic matter in wastewater into stable inorganic substances that donâ€™t provide pollution impacts on the environment. This study determines the best time for the aeration process to reduce Chemical Oxygen Demand (COD) or Biological Oxygen Demand (BOD) of animal feed wastewater and the volume ratio of waste, that is, the number of microorganisms to reduce COD and BOD of animal feed wastewater. The study results show that the longer the aeration contact time, the more significant the decrease in COD and BOD values. In addition, the greater the addition of microbial concentration, the more effective the reduction in COD and BOD values. Furthermore, the aeration process time with microbial concentration, which will produce the best COD and BOD reduction, is 6 hours. Unfortunately, the COD and BOD values ??still do not meet the wastewater quality standards in the aeration process. Still, with microbial concentrations, COD and BOD values ??reduction targets will be obtained in the aerobic biological process, following the wastewater quality standards. Finally, wastewater processing from the animal feed industry with a combination of aeration and aerobic biology can meet quality standards. Keywords: aerobic, anaerobic, animal feed, BOD, COD, wastewater Â  ABSTRAK Air limbah merupakan air yang tidak bersih atau yang mempunyai kandungan berbagai zat yang berbahaya bagi kelangsungan hidup manusia, hewan, dan tumbuhan. Biasanya limbah dihasilkan dari kegiatan manusia (termasuk industrialisasi) sehingga sudah sepatutnya perindustrian mengelola hasil buangannya sesuai kaidah pengolahan limbah secara terpadu, efisien, dan efektif. Aerasi merupakan salah satu teknik yang paling banyak digunakan dalam perbaikan karakteristik fisik dan kimiawi air limbah. Terdapat berbagai proses pengolahan limbah di mana salah satunya dengan memanfaatkan aktivitas mikroba aerob untuk menguraikan zat organik dalam kondisi aerob menjadi zat anorganik yang stabil yang tidak mencemari lingkungan. Tujuan dari penelitian ini adalah mengetahui waktu terbaik proses aerasi terhadap penurunan Chemical Oxygen Demand (COD) atau Biological Oxygen Demand (BOD) limbah cair pakan ternak dan mengetahui rasio volume limbah, yaitu jumlah mikroorganisme terhadap penurunan COD dan BOD limbah cair pakan ternak. Kesimpulan hasil kajian yaitu waktu pengontakan aerasi semakin lama dan penambahan konsentrasi mikroba berpengaruh pada penurunan nilai COD dan BOD dengan penurunan terbaik didapatkan pada waktu 6 jam. Nilai COD dan BOD proses biologi aerob dengan penambahan konsentrasi mikroba pada proses aerasi dan kombinasi aerasi dan biologi aerob telah memenuhi standar baku mutu limbah tetapi pada proses aerasi belum. Kata kunci: aerob, anaerob, BOD, COD, limbah cair, pakan ternak